Analisis Praktik Akuntansi Aktiva Tetap Berdasarkan Konsep Dasar Akuntansi di PT Kereta Api Indonesia (Tahun 2023) - Aninda Nuraini; Anis Fitriyani; Faiz Azzam Attamimi; Siti Janiah; Siti Syawaliyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Fixed assets play an important role in supporting the operations of PT Kereta Api Indonesia (Persero) as a BUMN in the transportation sector. This study aims to evaluate the suitability of PT KAI's fixed asset accounting practices in 2023 with PSAK No. 16. This research uses a qualitative approach with descriptive and verification methods, using secondary data in the form of financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The data is analyzed through document studies and compared with the provisions of accounting standards and supported by relevant scientific references. The results showed that PT KAI has carried out the recognition, measurement, and presentation of fixed assets according to standards, using the straight-line method and the historical cost approach. The statement of financial position is also prepared based on the principle of balance between assets, liabilities, and equity in accordance with PSAK No. 1. This practice shows compliance with accounting standards, and reflects the company's commitment to accountability, transparency, and professional and trusted asset governance.